Failure cause analysis of an expansion bellow of integrated turbine unit. (June 2021) - Subramanian, Chidambaram; Roy, Himadri; Kumar, Abhishek; Mondal, Abhijit; Ray, Subrata; De, Sanjib Kr; Ghosh, Debashis; Saha, Atanu
Abstract: The bellow is a flexible component which compensates an expansion allowance imposed by axial strain during high temperature service. The bellow failure during turbine operation of boiler unit has been systematically investigated. The metallurgy of bellow was AISI 316L stainless steel. The comprehensive laboratory investigation includes visual inspection, chemical analysis, mechanical tests, metallographic and fractographic studies. Visual inspection in the field revealed multiple cracks in the bellow and failed debris were collected for laboratory investigation. The mechanical tests of the expansion bellow confirmed to material property specification. The microstructure revealed austenitic structure and fracture surface revealed striation marks. The striation marks attributed to fatigue failure. Finite element analysis revealed that maximum stress induced in the trough region and stress could be higher as compared to ASME VIII Div 1 design equations. It can be concluded that actual operating pressure range could resulted in sufficient stress cycles to initiate fatigue cracks from surface of the bellow. The large number of stress cycles owing to actual varied pressure range attributed to fatigue failure. It is recommended to reduce many intermittent operating conditions by good operational practice and installation of strain gauges at critical locations of the bellow. It is further proposed to increase the existing ply thickness and install reinforced expansion bellow & sandwich/layered plies for prevention of fatigue failure. Highlights: Expansion U-bellow in integrated turbine unit failed after nine years of service. Striation marks attributed to fatigue failure. FEA shows that maximum stress induced in trough region of the bellow. Varied operating pressure ranges of line pipe resulted in sufficient number of stress cycles in bellow.